Influence of MicroCT Resolution and Segmentation Techniques on Porosity Analysis in Carbonate Rocks - Olga M. O. Araújo; Alessandra Silveira Machado; Cíntia Ferreira; Davi F. Oliveira; Ricardo Tadeu Lopes (e-Journal of Nondestructive Testing)
MicroCT images can be used to perform 3D visualization and quantitative analysis in a nondestructive manner. In this work, digital images were used to characterize the porosity of a carbonate rock sample. The resolution is essential due to the necessity to capture important microstructures. Lacustrine carbonate rocks form hydrocarbon accumulations, some of which are contained in oil fields and coquinas are one of the main reservoirs. The complexity and heterogeneity of these samples turn a difficult characterization and the internal structures of these deposits make them a challenge in terms of reservoir description. The use of digital data on porosity analysis is essential for rock structure characterization. To evaluate the impact of the binarization process and the effective pixel size we perform morphology analysis with different methods for segmentation on a sample of coquina with the different pixel size of 6, 10, 14 and 18μm. The results present differences for porosity compared to experimental data and shows that the resolution is important to capture the microporous and consequently the total porosity. Furthermore, was possible to calculate the pore size distribution for each effective pixel size resolution and segmentation process in coquina rock.